Environmental Effects on Milk Yield Traits in Brown Swiss Herd Raised at Mus - Alparslan State Farm in Turkey - Seker, Ibrahim; Tasali, Hasan; Bayraktar, Metin; Saatci, Mustafa; Tilki, Muammer (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
Study was conducted to define the effects of some environmental factors on lactation length and milk production in Brown Swiss cattle reared in Mu Alparslan State Farm. For this aim 768 lactation records belonging 282 cattle between the years of 1989 and 2004 were used. Means of milk production, 305 day milk production and lactation length of the cows in the study were defined as 4002.44 +/- 42.41 kg, 3892.59 +/- 37.34 kg ve 300.51 +/- 1.86 day respectively. Year, season and lactation number significantly affected the milk yield and 305 day milk yield (p < 0.05, P < 0.01). Similarly, statistically significant effects of year and lactation number on lactation length were defined (P < 0.01).
Keywords: Swiss-Brown; Milk production; Lactation period; Environmental factors